2016
DOI: 10.1038/srep36839
|View full text |Cite
|
Sign up to set email alerts
|

Ecological dynamics of influenza A viruses: cross-species transmission and global migration

Abstract: A comprehensive study of cross-species transmission and inter-regional migration would provide insights into the global ecology of influenza A viruses (IAVs). To this end, we assembled 17,241 non-redundant IAV whole-genome sequences with complete epidemiological information. We hierarchically divided the movements of IAVs into the cross-species transmission in each region and the inter-regional migration driven by each host species. We then systematically identified the potential cross-species transmission and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 41 publications
0
22
0
Order By: Relevance
“…The distribution of migratory birds, density of swine in some major migration flyways, transcontinental pig movement, and global live-swine trade (Nelson et al, 2015b; Ren et al, 2016) make these rare events in swine important to detect and investigate before the novel virus can be widely disseminated or contribute internal genes to endemic swine strains. Fortunately, in this case, the virus quickly disappeared from the source herd and no other detections were found in any other swine herds submitting samples to the ISU Veterinary Diagnostic Lab or in herds participating in the USDA IAV swine surveillance program.…”
Section: Discussionmentioning
confidence: 99%
“…The distribution of migratory birds, density of swine in some major migration flyways, transcontinental pig movement, and global live-swine trade (Nelson et al, 2015b; Ren et al, 2016) make these rare events in swine important to detect and investigate before the novel virus can be widely disseminated or contribute internal genes to endemic swine strains. Fortunately, in this case, the virus quickly disappeared from the source herd and no other detections were found in any other swine herds submitting samples to the ISU Veterinary Diagnostic Lab or in herds participating in the USDA IAV swine surveillance program.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in Australia, taxonomically related dabbling Grey Teals (Anas gracilis) and Pacific Black Ducks (Anas superciliosa) may share the environment with the distantly related filter feeding Pink-eared Duck (Malacorhynchus membranaceus). These multi-host flocks form multi-host maintenance communities [6], with consequences for virus ecology, transmission, and virulence [1,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…; Ren et al. ). On the other hand, several studies have reported evidence for a strong phylogenetic distance effect.…”
Section: Discussionmentioning
confidence: 98%
“…Little is known about the relative importance of (phylo) genetic versus ecological factors for host shifts, but it appears that this varies widely across systems. On the one hand, several pathogens (e.g., influenza viruses and Mycobacterium tuberculosis) have shifted between humans and domesticated animals such as cattle or fowl-species that are only distantly related to humans but have close physical contact (Smith et al 2009;Ren et al 2016). On the other hand, several studies have reported evidence for a strong phylogenetic distance effect.…”
Section: Discussionmentioning
confidence: 99%